Vitamin analysis for the health and food sciences - Eitenmiller, Ronald R. (CRC Press, 2000)
Employing a uniform, easy-to-use format, Vitamin Analysis for the Health and Food Sciences, Second Edition provides the most current information on the methods of vitamin analysis applicable to foods, supplements, and pharmaceuticals. Highlighting the rapid advancement of vitamin assay methodology, this edition emphasizes the use of improved and sophisticated instrumentation including the recent applications and impact of the widely adopted LC-MS. Designed as a bench reference, this volume gives you the tools to make efficient and correct decisions regarding the appropriate analytical approach--saving time and effort in the lab. Each chapter is devoted to a particular vitamin and begins with a brief review of its uniqueness and its role in metabolism. The authors stress a thorough understanding of the chemistry of each compound in order to effectively analyze it and to this end provide the chemical structure and nomenclature of each vitamin, along with tabular information on spectral properties. They supply extensive insight into practical problem-solving including an awareness of the stability of vitamins and their extraction from different biological matrices. All information is heavily documented with the latest scientific papers and organized into easily read tables covering topics necessary for accurate analytical results. After presenting the chemistry and biochemistry of the vitamin, each chapter details the commonly used analytical and regulatory methods. A summary table gives at-a-glance information on many of these sources, as well as several of the AOAC International Methods. In addition the authors apply their extensive experience in the field to create a critical, interpretive review of the advanced methods of vitamin analysis with sufficient detail to be a valuable guide to cutting-edge methodology.